2000
DOI: 10.1215/s1522851799000332
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor-b in human astrocytoma

Abstract: Growth of human malignant gliomas is stringently dependent on an angiogenic process that probably involves vascular endothelial growth factor (VEGF). Expressions of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…VEGF, a well-described HIF-1␣ target gene, is strongly induced during development but is constitutively expressed at nearly undetectable levels in adulthood under normoxic conditions (2,5,28). VEGF is also upregulated during pathological processes in the brain (28,31,32) and in vitro (8,14,17,39). Indeed hypoxic exposure moderately increased cytoplasmic accumulation and basal release of VEGF in our astrocyte cultures in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 71%
“…VEGF, a well-described HIF-1␣ target gene, is strongly induced during development but is constitutively expressed at nearly undetectable levels in adulthood under normoxic conditions (2,5,28). VEGF is also upregulated during pathological processes in the brain (28,31,32) and in vitro (8,14,17,39). Indeed hypoxic exposure moderately increased cytoplasmic accumulation and basal release of VEGF in our astrocyte cultures in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 71%
“…VEGF is upregulated by hypoxia, which does not play a role in a cell culture system. However, not all isoform's of VEGF are regulated by hypoxia [45]. Our primer pair for quantitative RT-PCR is not able to distinguish between the different isoform's.…”
Section: Increased Decreasedmentioning
confidence: 89%
“…Previous studies observed that VEGF-C mRNA was highly expressed in other neurological diseases such as brain tumors (17,18,20,23). Grau et al (18) found that VEGF-C was mainly expressed in endothelial cells and other regions tightly associated with blood vessels in brain tumor tissues.…”
Section: Enhanced Expression Of Vegf-c In Cortical Tubersmentioning
confidence: 98%